Tax Competition and the Choice of Tax Structure in a Majority Voting Model - Rainald Borck (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
This note studies the choice of tax structure in a majority voting model with tax competition. Regions may tax mobile capital or immobile labor. Individuals differ with respect to their relative endowments of labor and capital. Even though a lump sum tax is available, the equilibrium capital tax in a jurisdiction may be positive. In a symmetric equilibrium, this will be true if the median capital endowment is smaller than average.
Keywords: D72; H77; 330; tax competition; voting; Steuerwettbewerb; Steuersystem; Public Choice; Abstimmungsregel; Theorie